Conforto ambiental e neuroarquitetura: avaliação pós-ocupação no contexto da covid-19 (Revista Brasileira Multidisciplinar, 2023)
The Covid-19 pandemic caused major impacts on the lives of individuals globally. As a result of the recommendation of social isolation, residences have become long-term environments, making it necessary to adapt them to meet new spatial demands. This scenario directly influenced the interaction of users with their homes, reflecting on the meaning of inhabiting and the living experience, resulting in changes in lifestyle that can impact the physical and mental health of individuals. In this context, this article shows the results of a study whose objective was to carry out a Post-Occupation Evaluation (POE) in residential environments, in the area of environmental comfort supported by neuroarchitecture strategies, to understand the physical space from the perspective of its users, since these is a key aspect in behavior, decision-making, and well-being. With this purpose, a questionnaire and the Wish Poem instrument were made available to the community. In this way, positive indicators of satisfaction of residents with their residences were obtained, however, the desires, symptoms and perceptions pointed out by users show that the environment is capable of harming physically and psychologically without being noticed. The analysis of the results indicates that pandemic's scenario showed that the residential environment is not static, requiring transformations according to transitory needs, making it necessary to (re)think the configuration of spaces, applying strategies of environmental comfort and neuroarchitecture, so that they can help users in their relationship with housing, providing health and well-being.
Keywords: post-occupancy evaluation; environmental comfort; neuroarchitecture; social isolation; Covid-19